Perianal mucinous adenocarcinoma with dysplastic polyps of the colon: A case report. (January 2021) - Feo, Claudio F.; Veneroni, Simone; Santoru, Antonio; Cossu, Maria Laura; Scanu, Antonio M.; Ginesu, Giorgio C.; Porcu, Alberto
Highlights: Mucinous adenocarcinoma of the perianal region is extremely rare (6.9% of anal neoplasms and 2–3% of all gastrointestinal malignancies). Given the low incidence of this tumor, it is often missed at initial evaluation. Association with chronic perianal fistula are common and inflammatory symptoms can be misleading with delay in diagnosis. The paucity of publications leads to a lack of consensus on both diagnostic and therapeutic approaches. The understanding of the etiopathogenic mechanisms may lead to the development of novel diagnostic and therapeutic protocols. Abstract: Introduction: Perianal mucinous adenocarcinoma is rarely encountered in the setting of anal neoplasms. The rarity of the disease and the paucity of publications on this topic are responsible for a lack of diagnostic and therapeutic guidelines. Presentation of case: An 80-year-old man with mucinous adenocarcinoma of the anal canal associated with dysplastic polyps of the colon was treated by multiple endoscopic polypectomies and abdomino-perineal resection of the rectum. We discuss the management of this rare case from the diagnosis up to one-year follow-up. Discussion: Perianal mucinous adenocarcinoma is a very rare entity frequently combined with chronic fistulas. Inflammatory symptoms may mislead its diagnosis, which is often delayed. The unique association between perianal mucinous adenocarcinoma and dysplastic polyps of the colon, that we have reported, may suggest a secondary etiology. High clinical suspicion is important for early and correct diagnosis, which should be based on endoanal ultrasound and/or magnetic resonance imaging followed by deep tissue biopsies. Conclusion: We stress the importance of accumulating such cases in the literature. The understanding of the etiopathogenic mechanisms may lead to the development of novel diagnostic and therapeutic protocols.